2022
DOI: 10.3390/ijerph191912941
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and Temporal Patterns of Ecological Connectivity in the Ethnic Areas, Sichuan Province, China

Abstract: With ongoing economic and social development, natural habitats are becoming increasingly fragmented, blocking habitat connections and reducing landscape connectivity. The study of changes in ecological connectivity can provide valuable information for habitat and landscape restoration, which are necessary for sustainable regional development. Despite the growing interest in this issue, studies that reveal the change in ecological connectivity in the compounded areas of ecological vulnerability and deep poverty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Ecological compensation aims to protect the ecological environment and to promote harmonious coexistence between man and nature [16,17]. Ecological compensation includes several aspects: first, economic compensation for the protection (restoration) or destruction of the ecological environment [18]; second, internalization of external ecological benefits and costs [19]; third, protection of ecosystems and environments for individuals or regions [20]; and fourth, making protective investments in areas or objects of great ecological value [21].…”
Section: Ecological Compensation Policymentioning
confidence: 99%
“…Ecological compensation aims to protect the ecological environment and to promote harmonious coexistence between man and nature [16,17]. Ecological compensation includes several aspects: first, economic compensation for the protection (restoration) or destruction of the ecological environment [18]; second, internalization of external ecological benefits and costs [19]; third, protection of ecosystems and environments for individuals or regions [20]; and fourth, making protective investments in areas or objects of great ecological value [21].…”
Section: Ecological Compensation Policymentioning
confidence: 99%
“…The western Sichuan ethnic region is located on the southeastern edge of the Qinghai Tibet Plateau, and it has become one of the largest areas of concentrated and deep poverty in China. This is due to the limitations of geography, regional culture, and transport bar-riers, which have led to the disadvantaged position of farming households in terms of social networks, employment opportunities, and economic resources, and have made their livelihoods more susceptible to instability and vulnerability [43,44]. In recent years, the rural residents' livelihoods based on rural natural resources have shown instability to the external environment due to the impacts of global climate extremes and the restructuring of the urban-rural spatial structure.…”
Section: Introductionmentioning
confidence: 99%
“…Fragmentation refers to the process by which a large continuous distribution of natural habitat is separated into many smaller patches by other unsuitable habitats under the influence of human activities and natural disturbances [ 11 , 12 ]. The multiple negative impacts of the fragmentation process, such as the reduction of natural habitat area, the reduction of connectivity between habitat patches, and the continuous decline of habitat quality, will pose serious challenges to human well-being and regional sustainable development [ 13 , 14 , 15 ]. Initially, a density-dependent reproduction and survival simulation model was developed, and it was concluded that the degree of fragmentation of nature reserves was positively correlated with the species extinction probability [ 16 ].…”
Section: Introductionmentioning
confidence: 99%